THE INFLUENCE OF SOCIAL MEDIA MARKETING AND ELECTRONIC WORD OF MOUTH ON REPURCHASE THROUGH BRAND IMAGE AS A MEDIATING VARIABLE ON AS FROZEN IN PALU CITY - Riga, Michael Regianto; Zahara, Zakiya; Kadang, Juliana (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2024)
The purpose of this study was to determine the effect of social media marketing on repurchase through brand image as a mediating variable and the effect of e-WOM on repurchase through brand image as a mediating variable at As Frozen in Palu City. As Frozen customers in Palu City were used as research objects. The sample of this study were consumers of As Frozen in Palu City. Researchers used a sample of one hundred respondents for this study. Purposive sampling is the sampling strategy used in this study, and SEM analysis is a data analysis method supported by the SmartPLS 4.0 program. The findings of this study show that each conjecture, namely, the conjecture regarding the effect of social media marketing on repurchase, brand image on repurchase, e-wom on repurchase, and brand image on repurchase has a positive effect that is empirically verified on all variables. Regarding the indirect relationship between variables, e-WOM on repurchase through brand image as a mediating variable and social media marketing on repurchase through brand image as a mediating variable both show a positive and significant relationship.